2022
DOI: 10.1021/acs.inorgchem.2c03924
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Manipulated Hydrolysis Process Assembles of Giant High-Nucleation Lanthanide-Oxo Cluster

Abstract: Widespread concern has been raised over the synthesis of highly nucleated lanthanide clusters with special shapes and/or specific linkages. Construction of lanthanide clusters with specific shapes and/or linkages can be achieved by carefully regulating the hydrolysis of lanthanide metal ions and the resulting hydrolysis products. However, studies on the manipulation of lanthanide-ion hydrolysis to obtain giant lanthanide-oxo clusters have been few. In this study, we obtained a tetraicosa lanthanide cluster (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…These findings showed that this temperature-decreasing χ m T value may be due to the decrease in the Stark sublevel of the Dy( iii ) excited state and the induced crystal-field effect. 33 Furthermore, the field-dependent magnetization of cluster 1 was tested at different temperatures (2–5 K) and applied fields of 0–7 T, and the M vs. H / T curves were plotted (Fig. 5b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings showed that this temperature-decreasing χ m T value may be due to the decrease in the Stark sublevel of the Dy( iii ) excited state and the induced crystal-field effect. 33 Furthermore, the field-dependent magnetization of cluster 1 was tested at different temperatures (2–5 K) and applied fields of 0–7 T, and the M vs. H / T curves were plotted (Fig. 5b).…”
Section: Resultsmentioning
confidence: 99%
“…26 Our research group has also made some progress in exploring the formation of high-nuclear lanthanide clusters. [29][30][31][32][33][34] For example, in 2019, we obtained Dy 10 nanoclusters with multiple relaxation behaviors by using Schiff base organic ligands having multidentate chelation coordination sites. After exploring their formation process, a step-bystep assembly mechanism was proposed by HRESI-MS. 29 We then constructed a cage-shaped cluster Dy 14 by connecting disc-shaped lanthanide clusters with strong hydrogen bonds and proposed its assembly mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Bond angles and bond lengths for Tb 2 Tb 2 are within the normal range of lanthanide clusters (Tables S1 and S2). …”
Section: Resultsmentioning
confidence: 99%
“…From this perspective, Ln III -based molecular cluster-aggregates (MCAs) have emerged as a suitable platform for luminescence at the nanoscale. In addition to a large number of emitting centers within a precise crystalline structure, MCAs offer excellent control over uniformity and composition. On top of that, the careful choice of a ligand moiety ensures, at the same time, core rigidity (which reduces phonon-assisted deactivation routes) and a suitable way to efficiently sensitize Ln III optical centers. The so-called “antenna effect” is essential to account for the low absorption coefficient of Ln III and accomplish high performance.…”
Section: Introductionmentioning
confidence: 99%